(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Differentiating between antemortem and postmortem injuries is of paramount importance for medical and legal rea sons. Wrong interpretation of injuries and subsequently the wrong cause of death would lead to a miscarriage of justice. Ideally in a fresh intact body the position and gross findings may indicate the cause and time of injury. Decomposition and dismemberment of a body will make difficult for subsequent identification. However, careful examination at autopsy helps in knowing the injury (antemortem or post-mortem) even in a decomposed or dismembered body. Here we report a case of a decomposed and dismembered body, where a diligent autopsy examination helped in correctly ascertaining the nature of injuries, the manner of death and thus aiding in apt execution of justice.